Manajemen Kepala Sekolah dalam Peningkatan Mutu Pendidikan SMP Negeri 14 Binjai - Marlenda, Vera; Sulasmi, Emilda; Dongoran, Faisal Rahman (EDUTECH, 2024)
This study aims to determine how the principal's management in improving the quality of education at SMPN 14 Binjai as well as its supporting and inhibiting factors as well as the steps taken in leading SMPN 14 Binjai. This study used qualitative descriptive method. The results of the research show that the first management function carried out by the principal in improving the quality of education is to plan the vision, mission and goals of the school which refers to graduation standards, standards of educators and education personnel, process standards and infrastructure standards. Furthermore, the school also organizes schools filled with the competent and responsible people. The implementation of the four education quality standards at SMPN 14 cannot be separated from the supervision of the principal and his person in charge. Improving the quality of graduates who have good attitudes, knowledge and skills, the school has prepared various activities in intracurricular, extracurricular and P5. Improving the quality of educators and education personnel is improved by conducting training and seminars at school and outside school as well as discussions and teacher learning community activities in schools. The school also provides full support for improving the competence of teachers and education personnel outside the school. Improving the quality of the learning process is carried out by moving class learning systems and the application of digitalization systems in classroom learning. Improving the quality of facilities and infrastructure is carried out by schools by trying to complete school facilities. Meanwhile, supervision is carried out by the principal by observing classes and asking for accountability reports on activities that have been carried out. The second result in the form of supporting factors for quality improvement is the competence of school principals, support from teachers, parents and the government and the existence of adequate facilities and infrastructure. Meanwhile, the blocking factors are internal factors from the principal, diversity of age and ability of teachers, passivity and lack of creativity of teachers and narrow land of SMPN 14 Binjai. The third result of the principal's success in leading is to have a solid team, go directly and be an exemplary example, build a positive work culture and allocate budgets effectively and efficiently.